ANALISIS SIKAP SOSIAL SISWA SEKOLAH DASAR PADA PEMBELAJARAN TEMATIK DENGAN MODEL INKUIRI TERBIMBING - Sudarsri Lestari; Erisy Syawiril Ammah; Eka Ramiati (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
Thematic learning can be strengthened by research based learning such as inquiry, so that collaboration can contribute to one another in building active and student-centered learning, and can have a positive influence on students' social attitudes. Based on the description, a study was conducted with the aim of: (1) knowing the implementation of thematic learning with the guided inquiry model; and (2) knowing students' social attitudes on thematic learning with the guided inquiry model. This study uses a qualitative approach, with field research designs. Data collection techniques using interviews, observation, and field notes. The results showed that: (1) teachers and students could carry out the thematic learning stages with guided inquiry models in learning 1 to 6 very effectively; and (2) students' attitudes towards thematic learning with guided inquiry models experience positive development. In learning 1, students' social attitudes are still dominant. While in learning 2, social attitude began to develop. Continued in learning 3 and 4, most of the social students begin to develop and culture, and in learning 5 and 6 the majority of students have a social attitude.